Kesalahan Pemakaian Bahasa Indonesia pada Unggahan Instagram Lokersolo - Achmad Rukani (FKIP, Universitas Palangka Raya, 2024)
Indonesian is used by the Indonesian people as a means of communication, both in oral and written form, in various media. A good Indonesian is an Indonesian that is not flawed and must comply with the rules. Unfortunately, it is not uncommon on some social media sites, especially Instagram, to still find errors in the use of language. This research aims to identify Indonesian language usage errors in @lokersolo's Instagram posts. The research method used is descriptive-qualitative. The data was taken from several Lokersolo account posts. The validity of the data was checked in two ways, namely Intrarater and Interrater. The results show that there are several forms of language errors in the writing of @lokersolo's Instagram posts, including: (1) Spelling errors, including capitalization errors and the use of italics; and (2) punctuation errors, such as the use of separation marks, inappropriate semicolons, and commas. (2) Dictionary errors, especially related to the use of foreign languages and inappropriate compound words (3) Errors in writing effective sentences, which are caused by a lack of parallelism or misalignment in sentences and a lack of logic in sentence construction. From the conclusion of the research results, it can be stated that the @lokersolo Instagram account pays more attention to the use of correct and effective Indonesian language in their uploads, including proper spelling, appropriate word selection, and the arrangement of logical and parallel sentences. This will improve the quality of communication and professionalism of the account in delivering information to its followers.